2021
DOI: 10.1080/07418825.2021.1879899
|View full text |Cite
|
Sign up to set email alerts
|

Small Local versus Non-Local: Examining the Relationship between Locally Owned Small Businesses and Spatial Patterns of Crime

Abstract: Irvine. His research interests focus on how neighborhoods change over time, how that change both affects and is affected by neighborhood crime, and the role networks and institutions play in that change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…At the same time, a high concentration of ethnic businesses can discourage crime by serving as a hub for immigrants to gather for work, promote social ties, and increase surveillance and guardianship in the community Stansfield, 2014). These ideas align with prior studies on the routine activities of micro places (e.g., census tracts, block groups), which find that while some businesses (e.g., bars, motels) are conducive to crime because of the services they provide or the clientele they attract, others suppress crime by increasing the social and economic viability of the area (Kim & Hipp, 2022;Papachristos et al, 2011).…”
Section: Immigrant-ethnic Activity Space (Ieas)supporting
confidence: 68%
“…At the same time, a high concentration of ethnic businesses can discourage crime by serving as a hub for immigrants to gather for work, promote social ties, and increase surveillance and guardianship in the community Stansfield, 2014). These ideas align with prior studies on the routine activities of micro places (e.g., census tracts, block groups), which find that while some businesses (e.g., bars, motels) are conducive to crime because of the services they provide or the clientele they attract, others suppress crime by increasing the social and economic viability of the area (Kim & Hipp, 2022;Papachristos et al, 2011).…”
Section: Immigrant-ethnic Activity Space (Ieas)supporting
confidence: 68%
“…Our findings of structural characteristics were consistent with our expectations and previous studies conducted in the US context. Furthermore, our interaction results highlighted that it is necessary to examine the different types of physical environment and structural characteristics simultaneously as suggested in previous studies (Kim & Hipp, 2021, 2022a,b). These results indicated that incorporating the physical and social environmental features based on the theoretical framework of criminal opportunities and social disorganization can be useful for understanding the spatial patterns of crime in Korean context.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, owners and employees of older businesses generally have worked longer in the same place; thus, they are more familiar with the area and the surrounding environment and know how to better monitor and regulate unwanted behavior (Kim & Hipp, 2021). Note that we do not know how long the same workers have been with a company, and our argument is only that, on average, older businesses are more likely to have long-term employees compared to newer businesses.…”
Section: Second Scenario: Guardianship Perspectivementioning
confidence: 93%
“…Therefore, it is more plausible to treat this group of cities included in the current study as one region where residents strongly share many realms of life, rather than viewing them as 80 individual cities. We nonetheless included city-fixed effects to account for baseline differences between these cities, similar to other studies (Hipp et al, 2019b;Kane et al, 2016;Kim & Hipp, 2021).…”
Section: Analytic Strategymentioning
confidence: 99%